CSF Hypocretin-1 Levels and Clinical Profiles in Narcolepsy and Idiopathic CNS Hypersomnia in Norway - Heier, Mona Skard (Associated Professional Sleep Societies, LLC, 2007)
OBJECTIVE: To evaluate the relationship between CSF hypocretin-1 levels and clinical profiles in narcolepsy and CNS hypersomnia in Norwegian patients. METHOD: CSF hypocretin-1 was measured by a sensitive radioimmunoassay in 47 patients with narcolepsy with cataplexy, 7 with narcolepsy without cataplexy, 10 with idiopathic CNS hypersomnia, and a control group. RESULTS: Low hypocretin-1 values were found in 72% of the HLA DQB1*0602 positive patients with narcolepsy and cataplexy. Patients with low CSF hypocretin-1 levels reported more extensive muscular involvement during cataplectic attacks than patients with normal levels. Hypnagogic hallucinations and sleep paralysis occurred more frequently in patients with cataplexy than in the other patient groups, but with no correlation to hypocretin-1 levels. CONCLUSION: About three quarters of the HLA DQB1*0602 positive patients with narcolepsy and cataplexy had low CSF hypocretin-1 values, and appear to form a distinct clinical entity. Narcolepsy without cataplexy could not be distinguished from idiopathic CNS hypersomnia by clinical symptoms or biochemical findings. CITATION: Heier MS; Evsiukova T; Vilming S; Gjerstad MD; Schrader H; Gautvik K. CSF hypocretin-1 levels and clinical profiles in narcolepsy and idiopathic CNS hypersomnia in norway. SLEEP 2007;30(8):969-973.